Oxcarbazepine as the initial monotherapy of focal epilepsy in adolescents and adults - T. N. Pushkar; A. M. Azhigova; P. N. Vlasov; A. B. Kozhokaru (Неврология, нейропсихиатрия, психосоматика)
Oxcarbazepine (OXC) is an antiepileptic drug (AED) used in children and adults as initial and adjunctive therapy for focal epilepsy (FE). It has been used in Russia since 2007; however, only a few studies have been published on its use in Russian patients to date.Objective: to assess the effectiveness and tolerability of OXC as initial therapy for FE in adults and adolescents, as well as to study epileptiform activity index (EAI) changes during treatment and its relationship with treatment effectiveness and tolerability.Patients and methods. We evaluated treatment effectiveness and tolerability and EAI in 89 adults with newly diagnosed FE aged 15–75 years for 12 months. Patients were divided into three subgroups according to the OXC treatment regimen. Side Effects of Anti-Epileptic Drugs (SIDAED) scale was used to assess treatment tolerability. Retention rate and seizure frequency changes were used to evaluate treatment effectiveness. EAI changes were assessed with video electroencephalography monitoring (4–24 h) during each visit (baseline, after 1, 3, 6, and 12 months).Results and discussion. The retention rate in patients on OXC monotherapy after 12 months was 71.9%, almost one-half of them (46.1%) achieved sustained remission. More than half of patients (52.9%) were prescribed 1200 mg/day of OXC, 12.3% – <1200 mg/day, and only in 6.7% of patients the dose exceeded 1200 mg/day. Side effects were observed in 9% of the cases. A 2.54-fold reduction in mean EAI index was observed during follow-up representing treatment effectiveness.Conclusion. OXC, as the initial AED for FE, has demonstrated high treatment effectiveness and tolerability. In addition, total EAI 2.5-fold reduction allows its usage as an additional quantitative marker of OXC treatment effectiveness.